Cytokine profile of Ehrlich ascites tumor treated with Bothrops jararaca venom - Da Silva, Reinaldo J. [UNESP]; Silva, Marcia Guimarães da [UNESP]; Vilela, Lízia C. [UNESP]; Fecchio, Denise [UNESP] (Wiley, 2002)
WE previously demonstrated that Bothrops jararaca venom (BjV) has an antitumor effect on Ehrlich ascites tumor (EAT) cells and induces an increase of polymorphonuclear leukocytes in early stages of tumor growth. It has been reported that this venom presents an important inflammatory effect when inoculated in animal models and in human snake-bites, and that cytokine levels have been detected in these cases. To evaluate whether the cytokines can be involved with the suppression of the tumoral growth, we evaluate the cytokine profile in the peritoneal cavity of mice inoculated with EAT cells and treated with BjV. Swiss mice were inoculated with EAT cells by the intraperitoneal route and treated with BjV venom (0.4 mg/kg, intraperitoneally), on the 1st, 4th, 7th, 10th, and 13th day. Mice were evaluated for cytokine levels on the 2nd, 5th, 8th, 11th and 14th day. Analysis was performed using an enzyme-linked immunosorbent assay for interleukin (IL)-1α, IL-2, IL-4, IL-6, IL-10, IL-13, and tumor necrosis factor-α (TNF-α) levels in the peritoneal washing supernatant. Results were analyzed statistically by the Kruskal-Wallis and Dunn's tests at the 5% level of significance. We observed that EAT implantation induces IL-6 production on the 11th and 14th days of tumor growth, IL-10 on the 11th day and TNF-α on the 14th day. The treatment with BjV suppresses production of these cytokines. In addition, IL-13 was produced by animals that were inoculated only with venom on the 11th and 14th days, and by the group inoculated with EAT cells and treated with venom on the 2nd and 14th days. Furthermore, we suggest that the IL-6 detected in the present study is produced by the EAT cells and the suppression of its production could be associated with the antitumor effect of BjV.
Keywords: Bothrops jararaca; Cytokines; Ehrlich ascites tumor; Snake venom; batroxobin; cytokine; interleukin 10; interleukin 13; interleukin 1alpha; interleukin 2; interleukin 4; interleukin 6; tumor necrosis factor alpha; animal experiment; animal model; antineoplastic activity; cancer inhibition; controlled study; enzyme linked immunosorbent assay; male; mouse; neutrophil; nonhuman; peritoneal cavity; priority journal; tumor growth; Animals; Carcinoma, Ehrlich Tumor; Crotalid Venoms; Interleukin-10; Interleukin-13; Interleukin-6; Male; Mice; Tumor Necrosis Factor-alpha; Animalia; Bothrops; Serpentes